IDENTIFIKASI IBU BERSALIN PEROKOK PASIF TERHADAP KEJADIAN PLACENTA PREVIA DI RUMAH SAKIT WILAYAH KABUPATEN KENDAL - Titi Mursiti; Tri Nurhidayati (Midwifery Care Journal, 2020)
The incidence of placenta previa has doubled in women who smoke. This happens because the carbon dioxide inhaled can cause placental hypertrophy, thereby affecting the development of the placenta. The purpose of this study was to identify maternal passive smokers against the incidence of placenta previa. This type of research is descriptive survey, which is a method carried out with the aim of describing a situation objectively. Method of sampling with accidental sampling as many as 20 respondents who experienced placenta previa in November 2107-May 2018. From the results of the study it can be concluded that mothers with placenta previa passive smokers as many as 15 people (75%) and mothers giving placenta previa non-passive smokers as many as 5 people (25%) in conclusion, there are 15 maternal mothers with placenta previa passive smokers (75%) in Kendal District Hospital. It is recommended for the community especially pregnant women if their husbands, family members or the surrounding community who smoke, should avoid or wear masks so that they are not exposed to cigarette smoke and do not interfere with pregnancy in childbirth later.